Три века русской поэзии: Сборник / сост. Н. В. Банников - Банников Николай Васильевич (Просвещение, 1986)
Содерж.: Авт.: М. Ломоносов, А. Сумароков, Г. Державин, Д. Фонвизин, Н. Карамзин, И. Крылов, А. Мерзляков, В. Жуковский, К. Батюшков, А. Пушкин. Экземпляры: (20190819) / Инвентарный номер: 12322 / Сис.шифр: Р1 / Авт.знак: Т 67 / ББК: 84(2Рос=Рус)